Social and Behavioral Science for Health Professionals - Hinote, Brian P.; Wasserman, Jason Adam. (Blue Ridge Summit : Rowman & Littlefield Publishers, 2019)
Social and Behavioral Science for Health Professionals examines various social and behavioral factors that affect health and illness, with a particular focus on how these phenomena inform clinical practice.
Neighborhood Disadvantage and the Role of Clinical PracticeConclusion; Activity-The Flint Water Crisis: The Many Dimensions of Class and Health; Discussion Questions; Chapter 5 A Matrix of Health Inequalities; Learning Objectives; Age; Gender; LGBTQ+; Race and Ethnicity; Culture; Conclusion: A Matrix of Inequalities; Activity-Historical Memory, Inherited Culture, and Distrust of Health Care: TheTuberculosis Outbreak in Marion, Alabama; Discussion Questions; Chapter 6 Health Behavior and Lifestyles; Learning Objectives; A Renewed Emphasis on Health Behavior; Explaining Health Behavior
Print version record.
The Health Belief Model
WorldCat record variable field(s) change: 072
Keywords: Social medicine; Health behavior; Medical personnel; Health behavior; Medical personnel; Social medicine; Medical: General; Electronic books